Successful Remembering Elicits Event-Specific Activity Patterns in Lateral Parietal Cortex - Kuhl, Brice A. (Society for Neuroscience, 2014)
Remembering a past event involves reactivation of content-specific patterns of neural activity in high-level perceptual regions (e.g., ventral temporal cortex, VTC). In contrast, the subjective experience of vivid remembering is typically associated with increased activity in lateral parietal cortex (LPC)—“retrieval success effects” that are thought to generalize across content types. However, the functional significance of LPC activation during memory retrieval remains a subject of active debate. In particular, theories are divided with respect to whether LPC actively represents retrieved content or if LPC activity only scales with content reactivation elsewhere (e.g., VTC). Here, we report a human fMRI study of visual memory recall (faces vs scenes) in which complementary forms of multivoxel pattern analysis were used to test for and compare content reactivation within LPC and VTC. During recall of visual images, we observed robust reactivation of broad category information (face vs scene) in both VTC and LPC. Moreover, recall-related activity patterns in LPC, but not VTC, differentiated between individual events. Importantly, these content effects were particularly evident in areas of LPC (namely, angular gyrus) in which activity scaled with subjective reports of recall vividness. These findings provide striking evidence that LPC not only signals that memories have been successfully recalled, but actively represents what is being remembered.